Whale worship in Vietnam and the role of youth - young intellectuals in creating, preserving and promoting the value of this religious heritage in the context of globalization and digital transformation - Van, Bui Thi Anh; Giang, Nguyen Minh; Diem, Tran Thi Hoai; Tam, Le Thi Thanh (Research Journal in Advanced Humanities, 2026)
Youth generally, and young intellectuals particularly, are unique segments and play particularly important role in almost societies. The religious heritage of worshiping Ca Ong is a special cultural heritage in the historical process of cultural exchange and acculturation in Vietnam. Although there have been many articles, topics, proceedings, books, thesises and dissertations on young intellectuals and youth from the perspective of sociology and psychology, there have also been many articles, topics, proceedings, books, thesises, and dissertations on the Ca Ong worship belief from the perspective of history - culture, there are almost no articles or research projects that give a worthy place to learning about the role of the young intellectual in the process of creating, preserving and promoting the values of religious heritage of worshiping Ca Ong. Therefore, this article wishes to add an important aspect about the characteristics of the creating, preserving and promoting the Ca Ong worship heritage in different periods.